Potential of Renewable Electricity from Biomass Waste of IIT Roorkee Campus, India - Dutt, Nitesh; Sharma, M.P. (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Abstract: Electricity production using conventional energy sources is associated with serious environmental problems like emission of pollutants, global warming and social problems. The world’s CO2 emissions are projected to rise from 29.0 billion MT in 2006 to 33.1 billion MT in 2015 and 40.4 billion MT in 2030. This increase in emissions indicates more global warming. The Indian Ministry of New and Renewable Energy (MNRE) has been supporting programs for the development of renewable energy sources which are not only unlimited but environmentally friendly — like biomass, solar, small hydro, wind, etc. If biomass is used sustainably, there is no net carbon emission over the time of a cycle of biomass production. Waste management is an important issue today. To handle the ever growing problem of waste, residents and companies are constantly looking for the best and least expensive methods. Types of waste generated by the Indian Institute of Technology Roorkee (IITR) include kitchen waste, municipal solid waste, sewage waste, and waste cooking oil. By utilizing biodegradable waste out of total waste clean energy can be generated and waste disposal problems solved. DOI: http://dx.doi.org/10.3126/hn.v9i0.7071 Hydro Nepal Vol.9 July 2011 38-43